2002
DOI: 10.1677/joe.0.1720177
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function and effect of aging in combined hetero/homozygous mice deficient in thyroid hormone receptors alpha and beta genes

Abstract: The maintenance of thyroid hormone (TH) homeostasis is dependent on the synthesis and secretion of TH regulated by TSH. This is achieved, in turn, by the negative feedback of TH on TSH secretion and synthesis, which requires the interaction with TH receptors (TRs). Derived by alternative splicing of two gene transcription products, three TRs (TR 1, TR 2 and TR 1) interact with TH while another, TR 2, binds to DNA but not to TH. In this study we compare the results of thyroid function tests in mice with deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…In addition, it has also been reported by our laboratory and others that absence of TR␤ does not cause such a decline in basal heart rates and, in fact, results in a slight increase in heart rate attributed to increased circulating levels of TH in these mice (Table 3) (15,19,20,33,35,36). However, there appear to be a number of differences in baseline heart rates of WT mice dependent on strain, even in papers by the same laboratories.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, it has also been reported by our laboratory and others that absence of TR␤ does not cause such a decline in basal heart rates and, in fact, results in a slight increase in heart rate attributed to increased circulating levels of TH in these mice (Table 3) (15,19,20,33,35,36). However, there appear to be a number of differences in baseline heart rates of WT mice dependent on strain, even in papers by the same laboratories.…”
Section: Discussionsupporting
confidence: 66%
“…These mice have disorganized chondrocyte columns and reduced width of the hypertrophic zone. However, they also have mild hypothyroxinemia (Macchia et al 2001, Weiss et al 2002, raising the possibility that the observed phenotype results from reduced local TH availability.…”
Section: Discussionmentioning
confidence: 99%
“…One can conclude that, in physiological conditions, most of the TRs (95%) are liganded in thyrotrope cells. The production of TSH in Pax8 / mice, which have very low TH concentrations and are deeply hypothyroid, is twice that in TR double-knockout mice (Weiss et al 2002a), suggesting that TRs exert aporeceptor activity in these cells. Remarkably, TR 1 but not TR seems to be responsible for aporeceptormediated activation of TSH (Sadow et al 2002).…”
Section: Role Of Apotrs In Adult Liver Heart and Pituitarymentioning
confidence: 98%